An Improved Counter-Forensic Algorithm to Erase the JPEG Compression Artifacts - Sheng, Guorui; Yang, Bo (International journal of mobile computing and multimedia communications, 2014)
With the growing awareness of the fraud case for digital images, the researchers have developed some forensic techniques that based on the intrinsic statistical history or trace left by the jpeg compression to determine an image's manipulation. Aiming at these forensic algorithms, special anti-forensic techniques was developed by removing footprints caused by jpeg compression. In this paper, the authors present an improved counter-forensic scheme that based on parameter adjustment. The simulation shows that by using the proposed strategy and combining the chaotic theory, the scheme can erase the quantization artifacts perfectly, even when the compression factor .